Screening of Cellulase Producing Strains and Study on Their Enzymatic Properties - Shili WU; Yingying XIE; Xuening DUAN; Manshi YE; Weiqi XU; Guidong HUANG; Xianfeng ZHONG; Hong REN (Shipin gongye ke-ji)
In order to obtain efficient cellulose degrading strains and enzyme resources, the microorganisms from traditional fermented food (white wine lees and sauce mash) were used as the research objects. The cellulase-producing strains were screened by plate screening using Congo red staining method and enzyme activity screening using 3,5-dinitrosalicylic acid method, and the cellulase-producing strains were subjected to colony morphological observation, physiological and biochemical characteristics and molecular biology identification, to investigate the enzyme production of the strains under different stress conditions, as well as the enzymatic properties of the cellulase produced by the strains. The results showed that a total of three strains with relatively high cellulase activity were screened, all of which were identified as Bacillus velezensis, with carboxymethylcellulase activity ranging from 109.37±6.89 U/mL to 125.97±4.37 U/mL. The enzyme production performance of the strains under different stress conditions showed that the enzyme activity of the strains showed a decreasing trend with the increase of salt content. When the salt content was greater than 9%, the enzyme activity could still be retained at 20 U/mL, and with the further increase of salt content, the enzyme activity basically remained unchanged. In the range of 0%~8% ethanol content, the enzyme activity of the strains showed an increasing and then decreasing trend, and the enzyme activity of all three strains were greater than 80 U/mL, among which, strain B12 had the highest enzyme activity at 6% ethanol content, and strains JL39, JL55 had the highest enzyme activity at 4% ethanol content. The enzymatic properties of cellulase showed that: The optimal reaction temperature of extracellular cellulase was 50 ℃; the optimal pH was 5.5~6.5; the metal ions Cu2+, Ca2+, and Mg2+ had a promotional effect on the enzyme activity of three strains, of which Cu2+ had the strongest promotional effect, while Fe2+, Mn2+, Fe3+, and Ni+ had a different effect on the enzyme activity. This study provides strain resources for the development and utilization of cellulase-producing strain resources, provides valuable enzyme resources for the efficient application of resistant cellulases, and lays the foundation for the transformation and utilization of biomass resources.